Determinants of volume status in peritoneal dialysis: A longitudinal study. Issue 10 (3rd May 2020) - Jaques, David A.; Davenport, Andrew
Abstract: Aim: In peritoneal dialysis (PD), fluid overload is frequent and associated with cardiac dysfunction and mortality. As it is considered a modifiable risk factor, we wished to describe clinical determinants of fluid overload in a longitudinal cohort of PD outpatients. Methods: We consecutively included PD outpatients treated with continuous ambulatory PD (CAPD) or automated PD (APD) attending for their routine clinical visit at a single tertiary hospital. Extracellular water (ECW) to total body water (TBW) ratio was measured by multifrequency bioelectrical impedance. Peritoneal transport characteristics were measured with a standard peritoneal equilibration test. Patients had a second follow‐up visit with the same measurements. Univariable and multivariable mixed linear regression models were conducted with ECW/TBW as the dependent variable. Results: A total of 155 patients were enrolled with a median follow‐up time of 12 months. Median dialysis vintage was 13.5 ± 3.4 months. Overall mean value of ECW/TBW was 39.3% ± 1.1. In multivariable analysis, factors positively associated with ECW/TBW were: Age ( P < .001), diabetes ( P = .002), and SBP ( P = .028). Factors negatively associated with ECW/TBW were: nPNA ( P = .001), serum albumin ( P < .001) and PTH ( P = .014). None of the considered variable showed a significant interaction with time. Conclusion: We confirm a high prevalence of fluid overload in PD patients and show that it is strongly associated with older age, diabetes, hypoalbuminemia and protein energy wasting. In contrast, when PD prescription is tailored to patient's individual characteristics, residual renal function, PD modality and peritoneal characteristics are not decisive in controlling volume status. SUMMARY AT A GLANCE: In a cohort of PD patients followed longitudinally, factors associated with poor volume control (i.e. overhydration) included older age, diabetes, hypoalbuminemia and protein energy wasting. More intriguingly, residual renal function, PD modality and peritoneal membrane transport characteristics have little obvious relation to extracellular volume status.